2013
DOI: 10.1021/ml400339b
|View full text |Cite
|
Sign up to set email alerts
|

Novel Indole-N-glucoside, TA-1887 As a Sodium Glucose Cotransporter 2 Inhibitor for Treatment of Type 2 Diabetes

Abstract: Inhibition of the renal sodium glucose cotransporter (SGLT) increases urinary glucose excretion (UGE) and thus reduces blood glucose levels during hyperglycemia. To explore the potential of new antihyperglycemic agents, we synthesized and determined the human SGLT2 (hSGLT2) inhibitory potential of novel substituted 3-benzylindole-N-glucosides 6. Optimization of 6 resulted in the discovery of 3-(4-cyclopropylbenzyl)-4-fluoroindole-N-glucoside 6a-4 (TA-1887), a highly potent and selective hSGLT2 inhibitor, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 22 publications
(32 reference statements)
0
32
0
Order By: Relevance
“…For analysis, we used TA-1887, an SGLT2i with selectivity for SGLT2 versus SGLT1, similar to canagliflozin. 11 , 12 To determine treatment effects, we evaluated db/db mice (also known as Lepr −/− mice) fed a HF diet as a model of severe diabetes and treated them with or without TA-1887. As reported by others, 13 , 14 in 1st month body weight of TA-1887-treated mice decreased relative to that of untreated mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For analysis, we used TA-1887, an SGLT2i with selectivity for SGLT2 versus SGLT1, similar to canagliflozin. 11 , 12 To determine treatment effects, we evaluated db/db mice (also known as Lepr −/− mice) fed a HF diet as a model of severe diabetes and treated them with or without TA-1887. As reported by others, 13 , 14 in 1st month body weight of TA-1887-treated mice decreased relative to that of untreated mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A previous report showed that phloridzin reduced glucose-induced GLP-1 release (Moriya et al, 2009). CGMI is reported to have more potent inhibitory activity against SGLT1 than canagliflozin (Nomura et al, 2014). We explored the effects of these compounds on plasma GLP-1 levels and intestinal carbohydrate absorption and evaluated the combined effect of canagliflozin and sitagliptin, a DPP4 inhibitor, in normal and diabetic rodents.…”
Section: Introductionmentioning
confidence: 99%
“…SGLT2 inhibitors have a glucose-lowing effect, but there is little risk of severe hypoglycemia due to SGLT1 reabsorption of glucose which occurs in the distal part of the proximal tubule [3]. One of the reasons the patient did not show severe hypoglycemia might be because she did not take other glucose-lowering agents at the same time which have been reported to induce severe hypoglycemia [6].…”
Section: Discussionmentioning
confidence: 99%
“…Since SGLT2 inhibitors inhibit glucose reabsorption by SGLT2, urine osmotic pressure increases due to increased urinary glucose excretion, causing osmotic diuresis, which affects urine output and body fluid volume [2]. Since these drugs do not directly affect glucose metabolism or insulin secretion in the body, SGLT2 inhibitor monotherapy does not cause severe hypoglycemia [3].…”
Section: Introductionmentioning
confidence: 99%